Pengaruh Kompetensi, Pengalaman Kerja, Independensi, Integritas, Profesionalisme, dan Akuntabilitas Auditor terhadap Kualitas Audit dengan Etika Auditor sebagai Variabel Moderasi (Studi pada Inspektorat 5 Kabupaten/Kota Provinsi Riau) - Risandy, Eka; Basri, Yesi Mutia; Rasuli, Muhammad (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2019)
This study aims to determine the effect of competence, work experience, independence, integrity, professionalism, and auditor accountability on audit quality with auditor ethics as moderation variables in Riau Province. This study uses 5 inspectorates namely Indragiri Hilir, Indragiri Hulu, Kuantan Singingi, Siak and Pekanbaru with a sample of 102 auditors. Data analysis uses moderated regression analysis. The results showed that the coefficient of determination (adjusted R-square) was 78.4%. This 78.4% of the auditor quality variable is influenced by competency, work experience, auditor independence, integrity, professionalism and accountability with the auditor ethics moderating variable. Hypothesis testing shows that competency (X1), auditor ethics (X7) has a partial effect on audit quality. While variables work experience (X2), integrity (X4), professional auditors (X5), accountability (X6) have no partial effect on audit quality independence variable (X3) has a partially negative effect on audit quality The results show that auditor ethics can moderate independent variable.